Media studies as an academic discipline (Internationalizing Media Studies, 2009)
The concept of ‘media studies’ or ‘media and communication’ is widely used in referring to an academic discipline established in universities as a major or minor subject, a department or institute and sometimes even a school or college. It is typically implied that this relatively young ﬁeld is by now a discipline in its own right alongside such traditional disciplines as history, literature, sociology and political science. However, the nature of the discipline remains unclear, while it is determined by administrative convenience and market demand rather than analysis of its historical development and scholarly position within the system of arts and sciences. This chapter discusses the nature of the discipline, using examples from Finland and other Nordic countries.